Prediction of Photovoltaic Power Based on SSA-BP Algorithm with Chaotic Mapping - Li, Zihan (E3S web of conferences, 2023)
Photovoltaic (PV) power generation is of great significance to the energy reform in China. In order to better grid-connect PV, maximize the utilization of light resources, and reduce the adverse effects on the power grid due to the uncertainty and randomness of light energy, we need to study the power generation of PV. This paper discusses the factors affecting the efficiency of PV power generation and the related prediction algorithms in the light of current literature and further uses software to optimize the algorithm for PV prediction.